FACILITIES AND INFRASTRUCTURE ADMINISTRATIVE GOVERNANCE ASSISTANCE TO IMPROVE SERVICE EFFICIENCY - Akhmad Mutamakin; Siti Munandhiroh; Idza Irawan (Institut Agama Islam Syubbanul Wathon Magelang, 2022)
This study aims to describe the current conditions regarding the administration of facilities and infrastructure in Babadan 01 hamlet, Patent village, dukun sub-district, Magelang district. This research was done because of the need for more socialization in the village apparatus about recording the administrative management of existing facilities and infrastructure. Thus, the first work program provided assistance and socialization to the community on the importance of recording the administrative management of hamlet facilities and infrastructure. The method used is PAR (participatory action research), meaning that this program was created because it needed to be strengthened by information obtained from the head of the hamlet and not the development of existing activities. This program has had a positive impact on both the hamlet and the surrounding community.